Bacterial ClpP Protease Is a Potential Target for Methyl Gallate - Zheng, Dehong; Xu, Yanan; Yuan, Gaoqing; Wu, Xiaogang; Li, Qiqin (Frontiers in Microbiology, 2021)
Methyl gallate (MG) is an effective microbicide with great potential application in the integrated management of plant diseases and an important potential drug for clinical application. However, its target remains unknown. This study conducted a transposon sequencing (Tn-seq) under MG treatment in plant pathogenic bacterium Ralstonia solanacearum. Tn-seq identified that the mutation of caseinolytic protease proteolytic subunit gene clpP significantly increased the resistance of R. solanacearum to MG, which was validated by the in-frame gene deletion. iTRAQ proteomics analysis revealed that chemotaxis and flagella associated proteins were the major substrates degraded by ClpP under the tested condition. Moreover, sulfur metabolism associated proteins were potential substrates of ClpP and were up-regulated by MG treatment in wild type R. solanacearum but not in clpP mutant. Furthermore, molecular docking confirmed the possible interaction between MG and ClpP. Collectively, this study revealed that MG might target bacterial ClpP, inhibit the activity of ClpP, and consequently disturb bacterial proteostasis, providing a theoretical basis for the application of MG.